Patterns of Self Poisoning by Household Substances ............................................................................IJMTFM (2011) 1(2):59-64 - Khokon, Kamruzzaman; Islam, Shadeque; Basher, Ariful; Amin, Robed; Faiz, Abul (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: Poisoning is an important public health problem in developing countries like Bangladesh; self poisoning with organophosphorous compound (OPC) used in agriculture is particularly common. However, tertiary level hospitals in urban settings, self-poisoning with different household substances is also frequent, especially in teenagers. This study aims to identify the common household substances used for self harm and describe their clinical profile. Methods: A prospective study was performed in five adult medicine units of Dhaka Medical College Hospital over a period of six months from January 2008 to June 2008. Data were collected purposefully in a standard case record forms. Results: One hundred and twenty eight patients with a definite history of self poisoning were enrolled. Majority of patients came from urban areas (77.4%); mean age was 20 years and 48.1% were unmarried. Most patients (102, 76.7%) were female. A suicidal intention was mentioned in 88.7% of cases and family disharmony (70.7%) was the main reported reason. Most of the patients (119, 89.4%) were educated with at least Primary school. The most commonly used compounds were Savlon (Chlorhexidine 0.05%, Cetrimide 0.5%) in 50.4% of cases and Harpic(Sodium alkyle benzene sulphonate & sodium alkene sulphonate) in 30.8% of poisoning cases. 92.5% of patients sought treatment in a public hospital. All patients received supportive and symptomatic treatment, commonly with intravenous fluids and omeprazole. Recovery was usually fast; 92.9% improved within two days. All patients survived and no complications were noted. Conclusion: Though poisoning due to household substances is usually mild, prompt recognition and early treatment is important. An effort should be made to define preventive measures that can be implemented in order to reduce this common form of self poisoning.